Is financial stress a facilitating factor in cartel formation? - Jesper Fredborg Huric-Larsen (Journal of Economic Criminology)
It is well-known that failing to achieve key organizational goals may pressure managers to commit fraud, but can it be a facilitating factor in cartel formation as well? The purpose of this study is to understand if firms known to have been in a cartel were under financial stress in the period leading up to the cartel formation. A trend analysis is used to examine the performance of the firms before, during, and after the cartel period. The study uses accounting data on firms belonging to sanctioned cartels. In addition, the data is used to determine if firms can achieve joint profit maximization and what happens to firm performance after the cartel is broken down. The results support the proposition that financial stress can be a motivating factor for cartel formation. Moreover, the results show that several firms fall short of benefitting from cartel participation and that cartel breakdown often leads to a worse than initial outcome. The conclusion is that financial stress increases the chances of firms engaging in cartel activity. And, that structural break analyses can likely detect cartels using trends in the performance of firms.